Dynamic response study of Ti3C2-MXene films to shockwave and impact forces. Issue 49 (6th August 2020) - Srivatsa, Shreyas; Belthangadi, Pavithra; Ekambaram, Shivakarthik; Pai, Manu; Sen, Prosenjit; Uhl, Tadeusz; Kumar, Saurabh; Grabowski, Krzysztof; Nayak, M. M.
Abstract : Ti3 C2 -MXenes films are subjected to dynamic phenomena of low and high-velocity impact resulting in fast response times with piezoresistivity behavior. Abstract : MXenes (Titanium Carbide, Ti3 C2 -MXene) are two-dimensional nanomaterials that are known for their conductivity, film-forming ability, and elasticity. Though literature reports the possibility of usage of Ti3 C2 -MXenes for sensor development, the material properties and response need be studied in detail for designing sensors to measure dynamic variables like force, displacement, etc., in a dynamic environment. Ti3 C2 -MXenes due to their good electro-mechanical properties can be used for manufacturing sensing elements for engineering and biomedical applications. This paper focuses on an investigation of the dynamic response properties of Ti3 C2 -MXenes subjected to shockwave and impact forces. A supersonic shockwave (Mach number: 1.68, peak overpressure: 234.3 kPa) produced in a shock tube acts as an external force on the Ti3 C2 -MXene film placed inside the shock tube. In the experiment performed, the response time of the Ti3 C2 -MXene film sample has been observed to be in the range of few microseconds (∼7 μs) for the high-velocity shock. In a separate experiment, Ti3 C2 -MXene film samples are subjected to low-velocity impact forces through a ball drop test. The results from the ball drop test provide a response time in the range of few milliseconds (average ∼1.5 ms). In this novel demonstration, the Ti3 C2 -MXene film sample responds well for both low-velocity mechanical impact as well as high-velocity shockwave impact. Further, the repeatability of the dynamic response of the Ti3 C2 -MXene film sample is discussed along with its significant piezoresistive behavior. This work provides the basis for sensor development to measure the dynamic phenomena of pressure changes, acoustic emissions, structural vibrations, etc.